Endophytic bacteria in the biological control of Spodoptera frugiperda - Sousa , Irisléia Pereira Soares de; Fernandes , Martielle Batista; Santos , Michelle de Oliveira; Matos , Amanda Dayanne Malta; Castro , Sabrina Gonçalves Vieira de; Almeida , Luciele Barboza de; Moura , Marielly Maria Almeida; Santos , Helena Souza Nascimento; Silva , Jaqueline Pereira Medeiros da; Mizobutsi , Edson Hiydu (Seven Editora, 2024)
The objective of this study was to evaluate the pathogenicity of bacteria isolated from neem, Azadirachta indica, on adults of Spodoptera frugiperda. All bacterial suspensions evaluated were calibrated to a concentration of 5.0 x 108 cells/mL. The adults evaluated were the survivors of caterpillars that ingested corn leaves treated with bacterial suspensions. With these surviving adults, couples were formed, which were kept in cages. The longevity of males and females, the pre-oviposition and fertile period, the total number of eggs, fecundity and fertility of females were evaluated. Of the total isolates evaluated, 64.0% of them caused some adverse effect to adults, to the point of affecting one or more of the variables evaluated. The ingestion of the bacteria by the caterpillars reduced the longevity of adults, both male and female. Females had a reduction in the fertile period, in the number of layings, in fecundity and in fertility. Only the pre-oviposition period was not affected. The isolates Bacillus sp. Epi 9, Bacillus subtilis and Neem 10 stand out because they affect the largest number of variables evaluated. The results obtained in this study are promising and important, as this is the first report of bacteria isolated from neem with pathogenic action to S. frugiperda. DOI:https://doi.org/10.56238/sevened2024.004-008